Republished: Is hypertension associated with job strain? A meta-analysis of observational studies. Issue 1065 (18th June 2014) - Babu, Giridhara R; Jotheeswaran, A T; Mahapatra, Tanmay; Mahapatra, Sanchita; Kumar, Ananth; Detels, Roger; Pearce, Neil
Abstract: Job strain results from a combination of high workload and few decision-making opportunities in the workplace. There is inconsistent evidence regarding the association between job strain and hypertension, and methodological shortcomings preclude firm conclusions. Thus, a meta-analysis of observational studies on hypertension among occupational groups was conducted to determine whether job strain was associated with hypertension. In January 2012, we carried out a comprehensive, topic-specific electronic literature search of the Ovid MEDLINE, EMBASE and PsychoINFO databases complemented by individual help from non-communicable disease experts. Experimental/interventional studies and studies on personality disorders were excluded. Nine of 894 identified studies met the eligibility criteria and were included in the meta-analysis. The pooled OR of the nine studies was 1.3 (95% CI 1.14 to 1.48; p<0.001), of case–control studies 3.17 (95% CI 1.79 to 5.60; p<0.001) and of cohort studies 1.24 (95% CI 1.09 to 1.41; p<0.001), all of which indicated statistically significant positive associations between job strain and hypertension. In a subgroup analysis, cohort studies of good methodological quality showed significant associations between job strain and hypertension, while those of poor methodological quality showed no association or subgroup differences. We conclude that despite methodological differences, case–control and cohort studies of good methodological quality showed positive associations between hypertension and job strain.